Integrating Hot Potatoes as a Digital Media to Develop Students’ Reading Skill - Armandini, Fadilla Zafa; Pusparini, Indrawati (UIBU, 2024)
The present study aims to analyze the integrating Hot Potatoes as a digital learning media in improving students’ reading skills in senior high school. The research was initiated due to students’ low interest and achievement in reading, coupled with the limited variations of instructional media commonly used by teachers. Hot Potatoes, a software for creating interactive exercises, provides various task types such as multiple-choice, matching, gap-filling, and crossword puzzles, which can potentially enhance students’ engagement. This study employed a Classroom Action Research (CAR) design conducted in two cycles, consisting of planning, action, observation, and reflection. The participants were 32 tenth-grade students from a senior high school in Malang. Research instruments included a reading test, observation checklist, and student response questionnaire. The findings revealed that integrating Hot Potatoes significantly improved students’ reading scores, as indicated by the increase in the average score from the pre-cycle to the second cycle. Students also demonstrated higher enthusiasm and motivation toward digital-based reading activities. Thus, Hot Potatoes proved to be an effective and engaging digital media for developing students’ reading skills. The study recommends that teachers incorporate interactive digital tools in reading instruction to enhance learning outcomes and student participation